Hoe is de wereld eraan toe : 1990 - Brown, Lester R.; Flavin, Christopher; Postel, Sandra; Starke, Linda; Liefrink, Jos (Antwerpen: Standaard Uitgeverij, 1990)
"Lester R. Brown; Christopher Flavin; Sandra Postel; Linda Starke; Jos Liefrink... et al. Aanwinst van De Batselier, NorbertOorspronkelijke titel : State of the World 1990"